2002
DOI: 10.1016/s0002-9440(10)61133-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-C5a Ameliorates Coagulation/Fibrinolytic Protein Changes in a Rat Model of Sepsis

Abstract: Multiple organ dysfunction syndrome is the leading cause of death in patients in surgical intensive care units and is accompanied by consumptive hemostatic changes often leading to disseminated intravascular coagulation (DIC), progressive complement activation, and unregulated release of pro-inflammatory mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 45 publications
5
89
0
3
Order By: Relevance
“…The evel of plasminogen activity in rats changes with age and sex of the animal, but it is much lower than those in humans. The parameters we measured in this study are comparable with those in the literature [26][27][28][29] . Plasminogen binds to fibrin as soon as a fibrin clot forms.…”
Section: Discussionsupporting
confidence: 88%
“…The evel of plasminogen activity in rats changes with age and sex of the animal, but it is much lower than those in humans. The parameters we measured in this study are comparable with those in the literature [26][27][28][29] . Plasminogen binds to fibrin as soon as a fibrin clot forms.…”
Section: Discussionsupporting
confidence: 88%
“…There are several lines of evidence supporting a role for C5a and its receptor, C5aR, in the coagulation process: Recent studies have implicated C5a in the procoagulant response associated with severe sepsis and remote organ injury in a rat cecal ligation and puncture model of sepsis (6). In vivo blockade using anti-C5a IgG results in amelioration of several fibrinolytic/coagulation protein changes occurring in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Both are considered among the earliest innate immune effectors that sense incoming inflammatory signals and are rapidly recruited to sites of injury and inflammation (3). Earlier studies have indicated a role for complement in procoagulant pathways by showing that interception of C5a and its receptor C5aR results in distinct changes in pro-/antifibrinolytic proteins (3,6) and in the induction of tissue factor (TF) in endothelial cells (7) and monocytes (8). Furthermore, studies in rodent models of APS-induced thrombophilia have indicated that activation of complement components C3 and C5 is required for the induction of thrombus formation (9 -11).…”
mentioning
confidence: 99%
“…The abnormal vitamin K-dependent factors are detected in rats by measuring coagulation time using the Kurata, Worldwide Safety Sciences, Pfizer Global Research and Development, Nagoya Laboratories, Pfizer Inc., 5-2 Taketoyo, Aichi 470-2393, Japan thrombotest [4, 6, 14, 18], the activity of coagulation factors [9,13], and descarboxyprothrombin (PIVKA-II) [7,8]. The hepaplastin-test is also employed to detect abnormal coagulation factors related to hepatic injury in rats [16,21].…”
Section: Abstract: a Battery Of Simple Tests For Profiling Abnormalitmentioning
confidence: 99%
“…One of the causes of this is decreased activity of vitamin K-dependent coagulation factors due to the generation of the inactive des-carboxyl form of coagulation factors, also known as "protein induced by vitamin K absence or antagonists (PIVKA)" [7,12]. Many chemicals are known to cause such abnormalities [8,20].The abnormal vitamin K-dependent factors are detected in rats by measuring coagulation time using the Kurata, Worldwide Safety Sciences, Pfizer Global Research and Development, Nagoya Laboratories, Pfizer Inc., 5-2 Taketoyo, Aichi 470-2393, Japan thrombotest [4, 6, 14, 18], the activity of coagulation factors [9,13], and descarboxyprothrombin (PIVKA-II) [7,8]. The hepaplastin-test is also employed to detect abnormal coagulation factors related to hepatic injury in rats [16,21].…”
mentioning
confidence: 99%